2022
DOI: 10.3390/ijms232012201
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Exosomes Released by Different Corneal Cell Types on the Wound Healing Properties of Human Corneal Epithelial Cells

Abstract: Corneal wound healing involves communication between the different cell types that constitute the three cellular layers of the cornea (epithelium, stroma and endothelium), a process ensured in part by a category of extracellular vesicles called exosomes. In the present study, we isolated exosomes released by primary cultured human corneal epithelial cells (hCECs), corneal fibroblasts (hCFs) and corneal endothelial cells (hCEnCs) and determined whether they have wound healing characteristics of their own and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 117 publications
(131 reference statements)
0
4
0
Order By: Relevance
“…There are some interesting studies analyzing this in the cornea. 13 , 14 , 31 , 32 Those studies also highlight that the basement membrane appears to limit EV diffusion, what could mean that the impact of EVs released by stromal cells may depend on the basement membrane integrity. However, in different diseases, epithelial function and structure is damaged, and basement membrane integrity can be affected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are some interesting studies analyzing this in the cornea. 13 , 14 , 31 , 32 Those studies also highlight that the basement membrane appears to limit EV diffusion, what could mean that the impact of EVs released by stromal cells may depend on the basement membrane integrity. However, in different diseases, epithelial function and structure is damaged, and basement membrane integrity can be affected.…”
Section: Discussionmentioning
confidence: 99%
“…The conjunctiva is composed of a stratified epithelium containing squamous epithelial cells and goblet cells and by a loose stroma containing, among other cells, conjunctival MSCs (Conj-MSCs). 12 There are several studies investigating ocular surface EVs, most of them focused on EVs derived from corneal epithelium, 13 15 with just one study analyzing conjunctival epithelial EVs. 16 Regarding ocular MSC-derived EVs, Shojaati et al showed that EVs isolated from MSCs from corneal stromal stem cells (CSSCs) had an essential role in the regeneration of the cornea after wounding.…”
mentioning
confidence: 99%
“…Experiments in transgenic mice with reduced Klf4 expression resulted in increased epithelial cell layers and a disrupted barrier function, highlighting Klf4's importance in maintaining the equilibrium between the stroma and epithelium [99]. This change is linked to the process of epithelial-to-mesenchymal transition [100]. The loss of Klf4 expression can engender worsening of stromal wounds and atypical transformation of keratocytes into myofibroblasts [101][102][103].…”
Section: Interactions Within the Stromal Stem Cell Nichementioning
confidence: 99%
“…The searching in this catalog of exosome donors is first refined by markers for the desirable molecules that will determine the vesicles performance in vivo [152,153]. The exosome source affects the exosome markers, which then guide the exosomes functionality [100]. Each of these steps will undoubtedly be the subject of future studies.…”
Section: Future Research and Therapy Perspectivesmentioning
confidence: 99%